The Gambia : 2010 Article IV Consultation; Staff Report, Statement by the IMF Staff Representative, Public Information Notice on the Executive Board Discussion, and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report, 2010)
The Gambian economy showed strong growth and low inflation during the global crisis under the Extended Credit Facility (ECF), despite a sharp drop in tourism and remittance receipts. Executive Directors appreciated the macroeconomic policy framework and stressed the importance of achieving the MDGs and targets on poverty-reducing expenditures. They encouraged strengthening of fiscal performance to anchor macroeconomic stability and reduce the debt burden. Directors strongly supported tax reform and welcomed budget procedures and their execution. Directors supported recent improvements in debt management and stressed the importance of debt sustainability.